Uma educação moral cristã : a atuação da congregação das Irmãs de Notre Dame em Maravilha-SC (1954-1976) - Vieira, Vitor Marcelo (2012)
This paper analyzes the performance of the Congregation of the Sisters of Notre Dame - Notre Dame (SND - Sisters of Notre Dame) in Wonder - SC, a city located in the extreme west of Santa Catarina. The SND was ahead of formal education in the locality implemented initially in the School gathered Vera Gomes de Miranda Group and then Our Lady of La Salette School between 1954 and 1976. Analyzing the arrival of SND to the site with their activities, it is clear that this event is characterized as one of the preponderant elements, undertaken ahead colonizatória. Nevertheless, such an event is not characterized as an isolated fact, but as a member of the same process with well-defined direction, ie, the desire to establish government "progress" and "development" in the region. This desire to occupy the space still has its roots in the occupation policy undertaken by the state, delegating the Settler, the company marketing the land. Besides analyzing the performance of SND in Wonder, this study considered the initial moments of the constitution of space and the consequent intention of Colonization in having the presence of SND. The sources used in this study derive from the very SND and are made up of documents and publications produced by the institution, such as annual reports, minutes of meetings and educational books of matches. To analyze this apparatus in the documentary We base the category of disciplinary power in Foucault (1997). Along with this, understand how they were shaping up relations in space colonization, with the actions of the State, with its interest in the settlement of the region and consequent incentive to Settler, was one of the goals. Nevertheless, identifying the discipline undertaken by SND in the classroom and the pedagogical meetings was mainly the basis of this text. Thus, through the analysis of primary sources to interpret the actions moralizing and diffusion of Christian principles undertaken by SND in the school and community.